2017
DOI: 10.1038/s41598-017-14475-w
|View full text |Cite
|
Sign up to set email alerts
|

Male fertility restored by transplanting primordial germ cells into testes: a new way towards efficient transgenesis in chicken

Abstract: The ongoing progress in primordial germ cell derivation and cultivation is opening new ways in reproductive biotechnology. This study tested whether functional sperm cells can be matured from genetically manipulated primordial germ cells after transplantation in adult testes and used to restore fertility. We show that spermatogenesis can be restored after mCherry-expressing or GFP-expressing primordial germ cells are transplantated into the testes of sterilized G0 roosters and that mCherry-positive or GFP-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 30 publications
(36 reference statements)
0
21
0
Order By: Relevance
“…In this study, EGFP-PGCs were derived from the germinal crescent as previously described (50). They were maintained in culture and stably transfected with a Cas9 construct which was mediated by phiC31 integrase as previously described (51). Briefly, 5 × 10 6 of EGFP-PGCs were resuspended in a total volume of 100 μl Nucleofector Solution V (Lonza, Switzerland) premixed with 10 μg of Cas9 plasmid and the same amount of phiC31 integrase.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, EGFP-PGCs were derived from the germinal crescent as previously described (50). They were maintained in culture and stably transfected with a Cas9 construct which was mediated by phiC31 integrase as previously described (51). Briefly, 5 × 10 6 of EGFP-PGCs were resuspended in a total volume of 100 μl Nucleofector Solution V (Lonza, Switzerland) premixed with 10 μg of Cas9 plasmid and the same amount of phiC31 integrase.…”
Section: Methodsmentioning
confidence: 99%
“…Since PGCs are precursors of sperm, researchers suggested that roosters could be used as recipient for exogenous transfer of genetically-modified PGCs which may improve the germline transmission rate (Trefil et al, 2017 ). Chicken embryos and adult roosters were chemically or physically sterilized to create a surrogate for external PGC donors (Trefil et al, 2006 ; Nakamura et al, 2008 , 2010 ; Ghadimi et al, 2017 ).…”
Section: State Of the Artmentioning
confidence: 99%
“…Performing injection of donor spermatogonial cells led to reestablishment of male function in 50% of the roosters only 5 weeks after injection (Trefil et al, 2006 ). Spermatogenesis was restored 4 weeks later in the case of PGC-transplantation compared to spermatogonial cells; however, PGCs exhibited higher efficiency in repopulating the seminiferous epithelium (Trefil et al, 2006 , 2017 ). This was very beneficial in the case of transplantation of genetically modified PGCs into mature roosters after complete irradiation (Trefil et al, 2017 ).…”
Section: State Of the Artmentioning
confidence: 99%
See 2 more Smart Citations